Altered expression of junctional proteins as a potential biomarker in oral precancerous and cancerous patients. Issue 2 (3rd April 2022) - Upadhaya, Puja; Giri, Sarbani; Barhoi, Dharmeswar; Bhattacharjee, Abhinandan
ABSTRACT: Due to a lower survival rate in patients with advanced clinical stages of oral cancer, discovering a biomarker that could diagnose and predict disease progression is vital. Cell–cell junctional proteins play a crucial role in the maintenance of tissue architecture but are often deregulated in different cancer. The present study investigates the expression of cell–cell junctional proteins viz : e-cadherin (E-cad) and zonula occludens-1 (ZO-1) in oral precancerous (OED) and cancerous (OSCC) patients to monitor if they can serve as practicable molecular markers. The ultrastructural junctional complex was studied by transmission electron microscopy, and the expression of proteins was performed by immunohistochemistry. The relationship between the expression of protein and clinicopathological features of the patients was checked by Pearson's correlation test. Furthermore, the survival curve of the follow-up data was estimated by the Kaplan–Meier method. We observed a disrupted junctional complex and a significantly decreased immunoexpression of E-cad and ZO-1 in OED and OSCC when compared to the adjacent non-cancerous tissues. The expression of ZO-1 was associated with TNM stages, whereas E-cad was associated with histological grades as well as TNM stages. A positive correlation was observed between the expression of ZO-1 and E-cad proteins in OED and OSCC. Further, follow-up studies revealed that high ZO-1 and E-cad expressing patients survived longer than their low expressed counterparts. The present study shows disruption of junctional complex and alteration of junctional proteins expression that could draw the attention of health professionals to explore junctional proteins as a possible therapeutic target in oral cancer.